Moral injury, moral resilience, and organizational effectiveness among nurse leaders: a descriptive analysis during the COVID-19 pandemic - Alanna J. Bergman; Ginger C. Hanson; Christian Jenkins; Katie E. Nelson; Danielle Boyce; Cynda H. Rushton (BMC Nursing)
Abstract Background While nurse leaders have a voice in some organizational decisions, their moral resilience and moral injury can be affected by organizational structures and processes during a public health emergency such as the COVID-19 pandemic. Purpose The purpose of this exploratory descriptive analysis was to characterize the differences and commonalities between types of nurse leaders and their experiences of perceived organizational effectiveness, moral injury, and moral resilience during the COVID-19 pandemic. Methods This was a quantitative study conducted via an online, national, cross-sectional survey. The survey included sociodemographic and professional practice questions, validated instruments measuring organizational effectiveness, moral injury, and moral resilience. Open-ended questions allowed participants to expand on topics of particular interest. Quantitative data were analyzed using ANCOVA models, qualitative data accompanies the quantitative results for descriptive elaboration. Results In total, 763 nurse leaders were included in the analysis. Executives scored higher on overall organizational effectiveness than other leaders but not nurse managers. Examining the differences in specific facets of organizational effectiveness revealed that nurse managers rated several aspects of staffing lower than executives. One-third of respondents met the threshold for clinically significant levels of moral injury (score ≥ 36). No significant differences were found between nurse leader roles on moral injury. ANCOVAs indicated that nurse executives had higher total moral resilience than either nurse managers (p = 0.030) or other leaders (p < 0.001). In the open-ended questions, nurse leaders discussed two additional facets of organizational effectiveness that affected moral injury and moral resilience: (1) inequity between healthcare workers in different roles, and (2) an imbalance between organizational finances and patient safety. Conclusion Organizations can promote retention and moral resilience among nurse leaders by cultivating trustworthy behaviors. This may be achieved through authentic communication and transparency, and by promoting the values reflected in the nursing code of ethics. Clinical trial number Not applicable.